Investigation of the Effects of Meteorin-Like Protein in a Model of Neuropathy Induced by Sciatic Nerve Injury - Tekin, Suat; Yuksel, Furkan; Ozcan, Mete; Sandal, Suleyman (Wiley, 2023)
[Abstract Not Available]
Keywords: METRNL; Neuropathy; Rotarod; Sciatic Nerve Injury